(untitled) (Research, Society and Development, 2023)
Maternal love is often seen as something instinctive, as an innate disposition of women. However, throughout history, the actions, behaviors, and role of mothers have undergone transformations, leading us to consider motherhood as a social phenomenon that adapts to specific sociocultural contexts. It is essential to recognize that maternal love is a social construct and is subject to changes and adjustments according to the needs and demands of society. With that said, the present study aims to analyze the sociocultural representation of motherhood, with a focus on the allegories present in the cultural process of constructing maternal instinct and love.